Abstract of: Sensitivity Study on Climate Induced Internal Pressure within Cylindrical Curved IGUs - Minxi Bao (Challenging Glass Conference, 2018)
Insulated glass units (IGUs) are employed in modern buildings as a substitute for monolithic glass to reduce heat loss through windows. In the past decades, the pursuit of higher aesthetic design drives glazed products evolving from conventionally flat into more creative and dynamic curved shapes. The call for curved IGUs brings up a series of challenges, and one remarkable issue is the determination of load sharing and glass stress when evaluating its structural  performance. Even though many national codes worldwide have established mature design approaches for load sharing of flat IGUs panels, such design approaches can scarcely be found for curved IGUs due to geometry complexity. In this paper, the author will use an FEA  tool along with automatic iteration scripts to carry out a sensitivity study on the internal climatic pressure of cylindrically curved IGUs, considering a series of geometrical variables. The paper aims to evaluate the relationships between the internal pressure and the geometrical parameters of curved IGUs and normalize all these parameters into a dimensionless chart.